MicroRNA-15a Carried by Mesenchymal Stem Cell-Derived Extracellular Vesicles Inhibits the Immune Evasion of Colorectal Cancer Cells by Regulating the KDM4B/HOXC4/PD-L1 Axis - Liu, Lei; Yu, Ting; Jin, Yanping; Mai, Wei; Zhou, Jing; Zhao, Chunbo (Frontiers in Cell and Developmental Biology, 2021)
The relevance of microRNA-15a (miR-15a) to autoimmunity has been reported. Herein, we intended to probe the potential roles of miR-15a shuttled by adipose-derived mesenchymal stem cells (adMSCs)-derived extracellular vesicles (Evs) in colorectal cancer (CRC). Initially, CRC cells were treated with interferon (IFN)-γ to screen out differentially expressed genes by transcriptome sequencing. Following a 24-h co-culture with 20 μM adMSCs-derived Evs, CRC cell viability, migration, invasion and apoptosis were assessed. After the determination of histone lysine demethylase 4B (KDM4B) as our target, its regulatory miRNA was predicted by the bioinformatics websites and verified by dual-luciferase and RNA pull down assays. Intriguingly, KDM4B downregulated homeobox C4 (HOXC4) expression, while HOXC4 bound to the promoter sequence of programmed death-ligand 1 (PD-L1). Thus, we conducted rescue experiments to study the role of KDM4B and HOXC4. Finally, we evaluated the effects of adMSCs on CRC cell growth and immune evasion through in vivo tumorigenesis experiments. AdMSCs-derived Evs overexpressing miR-15a repressed proliferation, migration, and invasion, whilst promoted the apoptosis of CRC cells via downregulation of KDM4B. These in vivo findings were reproduced in vitro on CRC immune evasion. Collectively, adMSCs-derived Evs overexpressing miR-15a restricted the immune evasion of CRC via the KDM4B/HOXC4/PD-L1 axis.